The bacterial world inside the plant - Santos, Roberta Mendes dos; Desoignies, Nicolas; Rigobelo, Everlon Cid (Frontiers in Sustainable Food Systems, 2022)
Sustainable agriculture requires the recruitment of bacterial agents to reduce the demand for mineral fertilizers and pesticides such as bacterial endophytes. Bacterial endophytes represent a potential alternative to the widespread use of synthetic fertilizers and pesticides in conventional agriculture practices. Endophytes are formed by complex microbial communities and microorganisms that colonize the plant interior for at least part of their life. Their functions range from mutualism to pathogenicity. Bacterial endophytes colonize plant tissues, and their composition and diversity depend on many factors, including the plant organ, physiological conditions, plant growth stage, and environmental conditions. The presence of endophytes influences several vital activities of the host plant. They can promote plant growth, elicit a defense response against pathogen attack, and lessen abiotic stress. Despite their potential, especially with regard to crop production and environmental sustainability, research remains sparse. This review provides an overview of the current research, including the concept of endophytes, endophytes in plant organs, endophyte colonization, nutrient efficiency use, endophytes and crop nutrition, inoculation with synergistic bacteria, the effect of inoculum concentration on plant root microbiota and synthetic communities. It also examines the practical opportunities and challenges when utilizing endophytes in the field of sustainable agriculture. Finally, it explores the importance of these associations with regard to the future of agriculture and the environment.